Spatiotemporal Analysis of Water Quality Using Water Quality Index and Heavy Metal Pollution Index: A Case Study of Al-Diwaniyah River, Iraq - Al Asadi, Safaa A. R.; Beg, Ayad Ali Faris; Al Kifarea, Hider M. A.; Bozdag, Ayla; Ghalib, Hussein B. (Iraqi Journal of Science, 2023)
The current study aims to assess the water quality of the Al-Diwaniyah River in the city of Al-Diwaniyah to drink in terms of chemical properties and heavy metals and their impact on the health of the local population. The results showed that most of the parameters in the river water are of low concentrations due to the limited human activities in polluting the river water. The study concluded that the water quality is suitable for drinking depending on major cations and anions in all seasons. The Heavy Metal Pollution Index (HPI) showed that the river water was clean and safe, except two slightly polluted samples. The study concluded that river water for drinking or various domestic uses does not pose any danger to human health if there are no other polluting factors.